Publicity's Secret : How Technoculture Capitalizes on Democracy - Dean, Jodi, 1962- (Book collections on Project MUSE., 2002)
In recent decades, media outlets in the United States - most notably the Internet - have claimed to serve the public's ever-greater thirst for information. Scandals are revealed, details are laid bare because "the public needs to know." In Publicity's Secret, Jodi Dean claims that the public's demands for information both coincide with the interests of the media industry and reinforce the cynicism promoted by contemporary technoculture. Democracy has become a spectacle, and Dean asserts that theories of the "public sphere" endanger democratic politics in the information age. Dean's argument is built around analyses of Bill Gates, Theodore Kaczynski, popular journalism, the Internet and technology, as well as the conspiracy theory subculture that has marked American history from the Declaration Independence to the political celebrity of Hillary Rodham Clinton. The author claims that the media's insistence on the public's right to know leads to the indiscriminate investigation and dissemination of secrets. Consequently, in her view, the theoretical ideal of the public sphere, in which all processes are transparent, reduces real-world politics to the drama of the secret and its discovery